2018
DOI: 10.3389/fimmu.2018.01607
|View full text |Cite
|
Sign up to set email alerts
|

Self-Damage Caused by Dysregulation of the Complement Alternative Pathway: Relevance of the Factor H Protein Family

Abstract: The alternative pathway is a continuously active surveillance arm of the complement system, and it can also enhance complement activation initiated by the classical and the lectin pathways. Various membrane-bound and plasma regulatory proteins control the activation of the potentially deleterious complement system. Among the regulators, the plasma glycoprotein factor H (FH) is the main inhibitor of the alternative pathway and its powerful amplification loop. FH belongs to a protein family that also includes FH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 196 publications
(272 reference statements)
0
65
0
1
Order By: Relevance
“…This cluster, which originated from incomplete genomic duplications of exons coding for CFH domains SCR6-8 and SCR18-20, contains long dispersed repeat elements (34). Due to this, the CFH-CFHR gene cluster is genetically instable, and all six proteins within it share very high sequence homology (34,45). In addition, various genetic studies have identified this locus as a region enriched with common and rare mutations associated with susceptibility to AMD, aHUS, C3G, IgA nephropathy, and SLE (45).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This cluster, which originated from incomplete genomic duplications of exons coding for CFH domains SCR6-8 and SCR18-20, contains long dispersed repeat elements (34). Due to this, the CFH-CFHR gene cluster is genetically instable, and all six proteins within it share very high sequence homology (34,45). In addition, various genetic studies have identified this locus as a region enriched with common and rare mutations associated with susceptibility to AMD, aHUS, C3G, IgA nephropathy, and SLE (45).…”
Section: Discussionmentioning
confidence: 99%
“…Due to this, the CFH-CFHR gene cluster is genetically instable, and all six proteins within it share very high sequence homology (34,45). In addition, various genetic studies have identified this locus as a region enriched with common and rare mutations associated with susceptibility to AMD, aHUS, C3G, IgA nephropathy, and SLE (45). One of the best studied genetic variations within the CFH is rs1061170, a nonsynonymous SNP, which results in the exchange of T to C in exon 9 and leads to substitution of tyrosine to histidine in position 402 (SCR7) in CFH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, other forms of familial C3 GP have been related to rearrangements of the CFHR2-CFHR5 hybrid gene and abnormalities in CFHR1 and CFHR5 [39,40], suggesting that the CFHR1-5 gene family should be carefully assessed in all C3 GP cases. A detailed description of the methods to quantify the CFHR proteins in the serum and detect circulating autoantibodies has recently been published by Sanchez-Corral et al [56].…”
Section: Diagnosismentioning
confidence: 99%
“…On the other hand, the fluid-phase regulators Factor H (FH) and FH-like 1 (FHL-1) inhibit the AP [35]. In addition, the more recently discovered FH-related proteins (FHRs) are believed to fine tune the regulatory capacity of FH; however, in vivo evidence is lacking, and in vitro evidence is often contradicting [36]. Most cells express several membrane-bound regulators like complement receptor (CR) 1, CD46 (also known as membrane cofactor protein [MCP]), CD55 (also known as decay-accelerating factor (DAF), and CD59.…”
Section: The Complement Systemmentioning
confidence: 99%